Optimalisasi Pendidikan Bahasa Arab Melalui Hilirisasi Pembelajaran Berbasis Konten Digitalisasi Islami: Mengoptimalkan Pendidikan Bahasa Arab Melalui Penerapan Pembelajaran Berbasis Konten: Digitalisasi Islam - Sriwahyuningsih R. Saleh; Roymanto Ilolu; Febrianto Hakeu (Language Development Center, 2026)
Background: The rapid development of digital technology and the challenges of learning Arabic, which is often perceived as abstract, require innovation through a contextual approach based on Islamic digital content. Purpose: This study aims to examine how Islamic digital content can be implemented to support a digital, relevant, and sustainable Arabic learning ecosystem for younger learners. Method: This study employed a qualitative case study design involving 28 students at MA Muhammadiyah Gorontalo City. Data were collected through in-depth interviews, participant observation, and document analysis over four months. Data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion verification through source triangulation. Results and Discussion: The implementation of downstream Islamic digital content was found to transform Arabic learning into a more active and contextual process, as reflected in higher participation in online discussion and reported improvement across students’ four language-skill areas. Downstream strategies involving collaborative content production, multi-platform distribution, and continuous evaluation were found to support the development of a more comprehensive digital learning ecosystem. The integration of Islamic values in digital content not only supported language development but also contributed to the strengthening of students’ Islamic character, while helping bridge the gap between conventional learning and the digital needs of the modern era. Conclusions and Implications: Downstreaming Islamic digital content appears to be a promising strategy for optimizing Arabic language education in the digital era. The study suggests the need for systematic policies to support digital transformation in Islamic educational institutions and the adaptation of similar models for other subjects.